The learning curve for robot-assisted radical cystectomy with total intracorporeal urinary diversion based on radical cystectomy pentafecta - Noh, Tae Il; Shim, Ji Sung; Kang, Sung Gu; Cheon, Jun; Pyun, Jong Hyun; Kang, Seok Ho (Frontiers in Oncology, 2022)
Objective: To analyze the learning curve for robot- assisted radical cystectomy (RARC) with total intracorporeal urinary diversion (ICUD) in terms of both time efficiency and quality of surgery based on radical cystectomy (RC)-pentafecta. Patients and Methods: We identified 203 consecutive patients who underwent RARC with ICUD of the ileal conduit (IC, 85) and orthotopic neobladder (ONB, 118) performed by a single surgeon between 2011 and 2021. We grouped ten consecutive patients into time-associated blocks according to the operation order. Process efficiency and operation quality were measured based on the surgeon’s console time and attainment/score sum of RC-pentafecta. The overcoming point of the learning curve was defined graphically and statistically. Results: The mean follow-up period was 44.5 ± 30.7 months. Of the 203 patients, 109 (53.7%) attained the five criteria of RC-pentafecta( ONB vs IC, 50.6% vs. 55.9%, p = 0.35). The attainment rate and sum of the RC-pentafecta score of the third group were not significantly different from those of all patients (40.0% vs. 53.7%, p = 0.369, 4.00 ± 1.05 vs. 4.41±0.75, p = 0.137, respectively), and the proficiency in operation quality was satisfactory in the third group. The console times continually improved and stabilized after the 140th case (IC, 60; ONB, 80), and the attainment rate and sum of the RC-pentafecta were significantly different between before and after the 140th case (p<0.001). Conclusion: A single surgeon’s learning curve for RARC with ICUD and pelvic lymph node dissection (PLND) showed an acceptable level of proficiency after 30 consecutive cases in terms of the operation quality. However, for an expert surgeon, 140 cases were required to reach a plateau in time efficiency and second leap with the RC-pentafecta. RARC with ICUD and PLND can be performed safely without compromising functional outcomes and complications through sharing and transmission of standardized techniques.